Maintaining the strength of the United States dollar in a strong free world economy - United States (Washington : For sale by the Supt. of Docs., U.S. Govt. Print. Off., 1968)
It is the purpose of this report to give some measure of vital understanding of the Action Program of the U.S Treasury Department and its importance to the people of the United States and peoples everywhere.
usc 13/06/18
Loans
Keywords: Balance of payments; Foreign exchange